Development Of an Energy-Aware Wireless Sensor Network Model for Enhanced Node Coverage and Reduced Energy Consumption - Dr. K.V. Vara Prasad,; S. Thasmiya Anjum,; K. Tabasum Sulthana,; Ramineni Usha,; M. Sai Sucharitha, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
We're seeing a growing demand across various sectors, from agriculture to monitoring urban infrastructure. To boost the reliability of data transmission and enhance energy efficiency, researchers are focusing on developing and fine-tuning energy-efficient coverage strategies for the nodes in these networks. This paper dives into creating a model for energy-efficient sensor node coverage, ensuring that every monitoring point is adequately covered by at least one sensor node. It does this through a thorough investigation of both hierarchical and flat routing protocols. Moreover, the study explores an energy-efficient coverage technique that leverages an upgraded gray wolf algorithm, aiming to optimize how sensor nodes are deployed and improve their coverage efficiency. The findings indicate that this algorithm achieves 100% coverage of target monitoring locations and significantly enhances network coverage optimization. The enhanced gray wolf algorithm stands out with the lowest standard deviation and impressive average performance, especially under a 30-dimensional condition.
Keywords: Wireless Sensor Network; Node Coverage; Improved Grey Wolf Algorithm; ACO Routing Protocol; Monitoring Area